Münster, LWL-Museum für Kunst und Kultur, Lichtkunstwerk 'Silberne... - Dietmar Rabich (Wikimedia Commons, 2022)
Notice iconographique issue de Wikimedia Commons. Titre: Münster, LWL-Museum für Kunst und Kultur, Lichtkunstwerk "Silberne Frequenz" – 2022 – 4266. Detail of the sculpture Silberne Frequenz (Otto Piene, 1970/71, redesign 2012/14) at the LWL Museum for Art and Culture, Münster, North Rhine-Westphalia, Germany Otto Pienes sculpture Silberne Frequenz (Silver Frequency) stands in front of the LWL Museum of Art and Culture in Münster. It was installed in 2014 as part of the museums renovation and the redesign of the forecourt. Piene, co-founder of the ZERO group, worked with light, movement, and immaterial effects. The sculpture consists of slender, silver-reflecting metal elements that come together to form a dynamic, wave-like shape. Its appearance changes depending on the incidence of lightreflections create the impression of vibration and energy. The title refers to frequencies as a symbol of exchange and communication. In the course of later redesigns of the square, the sculptures surroundings were rearranged | the work was preserved, but its effect in the space was slightly altered. The large LWL lettering on the forecourt was also discussed in this context. Critics perceived it as promotional and dominant over art and architecture, while supporters saw it as a clear identification of the museums location. The debate shows how sensitively the interplay between artwork, architecture, and public space is perceived.
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons